Clinical presentation of pediatric tuberculous spondylitis in high TB burden setting before and during the COVID-19 pandemic - Juslin, Nazhira P; Setiabudi, Djatnika; Nataprawira, Heda M; Ramdan, Ahmad (The Journal of Infection in Developing Countries, 2025)
Introduction: Tuberculous spondylitis (TBS) in children can be severe, non-specific, and slowly progressive. Disruptions in tuberculosis (TB) services were observed amid the coronavirus disease (COVID-19) pandemic, prompting a closer examination of its impact on TBS patients. This study compared the presenting symptoms of TBS in children before (A) and during (B) the pandemic. Methodology: An analytic retrospective study was conducted using medical charts and the pediatric respirology registry of all patients (aged ≤ 18 years) diagnosed with TBS before and after the pandemic. Demographic data, clinical features, confirmatory examination, and treatments were analyzed. Statistical significance was determined at p < 0.05. Results: The common presenting symptoms before and after the pandemic were gibbus (A 25; 93% vs. B 19; 79%, p = 0.232), back pain (A 20, 74% vs. B 20, 83%; p = 0.508), and inability to walk (A 15, 56% vs. B 16, 67%; p = 0.567). Involvement of ≥ 3 vertebrae was significantly more prevalent in group B (A 6, 23% vs. B 11, 46%; p = 0.09). The median time from symptom onset to diagnosis was longer in group B (A 13 weeks vs. B 21 weeks; p = 0.07). Conclusions: The pandemic had minimal effect on the clinical characteristics of TBS patients at presentation. However, most patients were in a serious condition at the time of presentation, suggesting that the symptoms had existed, but did not receive appropriate care from primary healthcare facilities. A meticulous assessment enabling early diagnosis and initiation of therapy is crucial.